Photoluminescence study of Eu3+ doped zinc-tungsten-antimonite glasses for red LED applications - Roy, Joy Sankar [UNESP] (2020)
The rare earth ions doped glassy materials have become crucial capstone in solid state lighting due to their top-notch optical properties. In this work, Eu3+ doped zinc-tungsten-antimonite glasses with compositions of (60 - x)Sb2O3 − 15WO3 – 25ZnO – xEu2O3 (where x is 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0) were prepared by melt quenching technique. The glasses were prepared with the variation of concentration of Eu3+ ions to achieve superior brightness. The emission intensity increases with the increasing concentration of Eu3+ ions. The prepared glasses exhibit strong hypersensitive red emission at 616 nm due to 5D0 → 7F2 transition under 465 nm excitation wavelength. Along with maximum bright red emission of 3 mol % Eu3+ doped glass also demonstrates high degree of excited state lifetime (556 μs). All these properties strongly validate the bright prospect of these luminescent glasses for utilizing in red LED applications.